A control method for hydraulic fracturing of the hard roof with long and short boreholes - Ma, Jinkui; Li, Hong; Guo, Xiaomin; Tian, Fuchao; Guo, Huaiguang (Frontiers in Materials, 2022)
During the mining of the working face, the hard roof can lead to a series of problems, such as air leakage in goafe, gas emission and concentration, casualties, damages to buildings and ecological environment and etc. The treatment of hard roof has always been a difficult problem in major coal producing countries. Although many scholars have conducted some theoretical research and field practice in this field in recent years, the above safety problems still occur frequently. In order to understand the mechanism of crack propagation caused by hydraulic fracturing of the roof, based on the theoretical analysis of linear elastic fracture mechanics and coal rock mechanics, the shear fracture criterion was determined for the formation of horizontal fractures in the natural cracks. Meanwhile, the conditions for the propagation of water-induced cracks in coal strata were considered when the crack tip was anisotropic and the coal and rock fracture surface adhesion force and water leakage in the crack surface. The formation of cracks is a process of vertical main cracks and the extended-airfoil branch cracks interconnecting with each other transversely and longitudinally, additional effect of hydrodynamic water wetting, to achieve the goal of structural transformation and slight weakening of coal and rock mass. According to the bidirectional stress of coal and rock mass, the maximum principal compressive stress of crack opening was calculated, and the propagation mechanism of hydraulic fracturing cracks in hard roof was obtained. The hydraulic fracturing technology for controlling hard roof was illustrated, and has been applied in No. 2 Well of Sihe Coal Mine for many years. The research results could provide reference for the control of hard roof in other similar mines.